2022
DOI: 10.3390/nu14132745
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement Use in Relation to Socio-Demographic and Lifestyle Factors, including Adherence to Mediterranean-Style Diet in University Students

Abstract: The study aimed to examine socio-demographic and lifestyle determinants, including diet quality, of dietary supplement (DS) use among 2545 students who attended public universities in Warsaw. The data was collected using a self-administered health and lifestyle questionnaire and a 5-day dietary record method. Diet quality was assessed using a Mediterranean Diet Score. To determine the covariates of DS use, multivariate-adjusted logistic regression models with an estimation of odds ratios (ORs) and 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
3
5
1
1
Order By: Relevance
“…Specifically, the most frequently used DS were multivitamins (MV) and vitamin C . Our results are in agreement with several other studies that were conducted before the pandemic with regards to the popularity of MV [ 16 , 18 , 29 , 30 , 31 , 33 , 45 ] and vitamin C [ 18 , 33 , 35 , 44 , 45 ], with few exceptions [ 19 , 27 , 43 ]; even after the onset of the pandemic, the popularity of MV [ 10 ] and vitamin C [ 20 , 35 , 36 ] remained high. The consumption of MV might be an attempt to cover the needs for a large extent of nutrients and, therefore, provide a broader sense of safety to the consumers who seek to take care of their general health; oddly enough, the men tended to consume MV more often even though most of them had fitness-related goals This finding is ambivalent, as it disagrees with the current literature [ 17 , 18 , 23 , 34 , 47 , 53 ], even though these studies seem to pool MV and multiminerals together; either way, even if we followed the same tactic, our results would still disagree.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Specifically, the most frequently used DS were multivitamins (MV) and vitamin C . Our results are in agreement with several other studies that were conducted before the pandemic with regards to the popularity of MV [ 16 , 18 , 29 , 30 , 31 , 33 , 45 ] and vitamin C [ 18 , 33 , 35 , 44 , 45 ], with few exceptions [ 19 , 27 , 43 ]; even after the onset of the pandemic, the popularity of MV [ 10 ] and vitamin C [ 20 , 35 , 36 ] remained high. The consumption of MV might be an attempt to cover the needs for a large extent of nutrients and, therefore, provide a broader sense of safety to the consumers who seek to take care of their general health; oddly enough, the men tended to consume MV more often even though most of them had fitness-related goals This finding is ambivalent, as it disagrees with the current literature [ 17 , 18 , 23 , 34 , 47 , 53 ], even though these studies seem to pool MV and multiminerals together; either way, even if we followed the same tactic, our results would still disagree.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the reasons for DS use, we found that, overall, the most common motivator was the improvement of physical condition, followed by the treatment of nutrient deficiencies and the treatment and prevention of pathological conditions. Our results are in agreement with similar pre-pandemic studies, which have found the main reasons for use to be “health” [ 18 , 44 , 45 ], the improvement of “health” [ 17 , 43 ] or “well-being” [ 46 ], the prevention or treatment of nutrient deficiencies [ 19 , 34 ], or a medical necessity [ 34 ]. However, other reasons, such as stress [ 47 ] and fatigue [ 27 ], have also been reported to be the prime motivator in certain studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…yaptığı bir çalışmada, Akdeniz diyetine uyum, diyet takviyesi kullanımı ile pozitif ilişkili bulunmuştur. 34 Çalışmada, öğrencilere gönderilen çevrim içi anketlerde yer alan sorular beyana dayalı olduğu için ve anketi yanıtlarken öğrencilerin gerçeğe uygun beyanda bulunmamış olma ihtimalleri, çalışmanın sınırlılığı olarak sayılabilir. Öğrencilerin COVID-19 pandemi sürecinde beslenme alışkanlıklarını, pandemi öncesi-sırasında besin destekleri kullanım durumlarını ve Akdeniz diyetine uyumlarını hem pandemi öncesinde hem de pandemi sırasında araştıran çalışma sayısı azdır.…”
Section: Bulgularunclassified